Root symbiotic fungi improve nitrogen transfer and morpho-physiological performance in Chenopodium quinoa - Alquichire-Rojas, Shirley; Escobar, Elizabeth; Bascuñán-Godoy, Luisa; González-Teuber, Marcia (Frontiers in Plant Science, 2024)
Root-associated fungal endophytes may facilitate nitrogen (N) absorption in plants, leading to benefits in photosynthesis and growth. Here, we investigated whether endophytic insect pathogenic fungi (EIPF) are capable of transferring soil N to the crop species Chenopodium quinoa. We evaluated nutrient uptake, carbon allocation, and morpho-physiological performance in C. quinoa in symbiosis with two different EIPF (Beauveria and Metarhizium) under contrasting soil N supply. A controlled experiment was conducted using two plant groups: (1) plants subjected to low N level (5 mM urea) and ( 2) plants subjected to high N level (15 mM urea). Plants from each group were then inoculated with different EIPF strains, either Beauveria (EIPF1+), Metarhizium (EIPF2+) or without fungus (EIPF-). Differences in N and C content, amino acids, proteins, soluble sugars, starch, glutamine synthetase, glutamate dehydrogenase, and physiological (photosynthesis, stomatal conductance, transpiration), and morphological performance between plant groups under each treatment were examined. We found that both Beauveria and Metarhizium translocated N from the soil to the roots of C. quinoa, with positive effects on photosynthesis and plant growth. These effects, however, were differentially affected by fungal strain as we as by N level. Additionally, an improvement in root C and sugar content was observed in presence of EIPF, suggesting translocation of carbohydrates from leaves to roots. Whereas both strains were equally effective in N transfer to roots, Beauveria seemed to exert less demand in C. quinoa for photosynthesis-derived carbohydrates compared to Metarhizium. Our study revealed positive effects of EIPF on N transfer and morpho-physiological performance in crops, highlighting the potential of these fungi as an alternative to chemical fertilizers in agriculture systems.